Search, effort, and locus of control - Andrew McGee; Peter McGee (Institute for the Study of Labor (IZA), 2011)
We test the hypothesis that locus of control - one's perception of control over events in life - influences search by affecting beliefs about the efficacy of search effort in a laboratory experiment. We find that reservation offers and effort are increasing in the belief that one's efforts influence outcomes when subjects exert effort without knowing how effort influences the generation of offers but are unrelated to locus of control beliefs when subjects are informed about the relationship between effort and offers. These effects cannot be explained by locus of control's correlation with unmeasured human capital, personality traits, and the costs of search - alternative explanations for the relationships between locus of control and search behavior that cannot be ruled out using survey data - as the search task does not vary across treatments, which leads us to conclude that locus of control influences search through beliefs about the efficacy of search effort. Our findings provide evidence that locus of control measures can be used to identify job seekers at risk of becoming discouraged and abandoning search.
urn:nbn:de:101:1-201109297463
Keywords: J64; D83; C91; 330; locus of control; reservation wages; labor market search; experiment; Arbeitsuche; Selbstevaluation; Anspruchslohn; Test